The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1002/jcla.23709
|View full text |Cite
|
Sign up to set email alerts
|

JNK pathway‐associated phosphatase associates with rheumatoid arthritis risk, disease activity, and its longitudinal elevation relates to etanercept treatment response

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 27 publications
3
18
0
Order By: Relevance
“…JKAP, as one key member of DUSP family, is reported to possess clinical value reflecting disease risk and severity of several immune/inflammatory‐related disease and neurological diseases. For instance, a study uncovers that serum JKAP is downregulated in rheumatoid arthritis patients compared to controls, and it is negatively correlated erythrocyte sedimentation rate, C‐reactive protein and disease activity in RA patients 6 ; another study discloses that blood JKAP reduction correlates with asthmatic exacerbation and pro‐inflammatory cytokines in asthmatic children 7 ; furthermore, some reports discovers that JKAP hypermethylation exists and correlates with TAU phosphorylation in AD patients, as well as is involved in the interaction between utero famine exposure and schizophrenia 9,10 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…JKAP, as one key member of DUSP family, is reported to possess clinical value reflecting disease risk and severity of several immune/inflammatory‐related disease and neurological diseases. For instance, a study uncovers that serum JKAP is downregulated in rheumatoid arthritis patients compared to controls, and it is negatively correlated erythrocyte sedimentation rate, C‐reactive protein and disease activity in RA patients 6 ; another study discloses that blood JKAP reduction correlates with asthmatic exacerbation and pro‐inflammatory cytokines in asthmatic children 7 ; furthermore, some reports discovers that JKAP hypermethylation exists and correlates with TAU phosphorylation in AD patients, as well as is involved in the interaction between utero famine exposure and schizophrenia 9,10 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we performed the current study and observed that serum JKAP was greatly decreased in PD patients compared to controls, correlates with lower UPDRS‐I score, UPDRS‐II score while higher MMSE score in PD patients. The possible explanations include: (1) JKAP insufficiency decreased neuro viability and function via its hypermethylation and inflammation regulation; therefore, it was downregulated in PD patients compared to controls, and correlated with some part of UPDRS scores 6–10 ; (2) JKAP inactivated T‐cell signaling and interacted with Th1 as well as Th17, resulting in aberrant immune environment and inflammation to affect PD progression; therefore, it correlated with some part of UPDRS scores and MMSE score 8,11–13,20,21 ; (3) JKAP repressed Th17 cell differentiation, the latter was closely involved in the cognitive impairment in neurological diseases including PD; therefore, JKAP correlated with MMSE score 22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, DUSP1 deficiency promotes inflammation and bone destruction in collagen‐induced arthritis 18 ; besides, DUSP5 represses autoimmune arthritis by regulating Th17/Treg balance and inactivating osteoclastogenesis in mice 19 . In aspect of DUSP22, although no experimental study been reported, two clinical studies revealed that circulating DUSP22 is closely involved in RA risk and progression 20,21 . In our present study, we observed that synovium DUSP22 level was decreased in RA patients compared knee trauma patients; furthermore, serum DUSP22 level was also reduced in RA patients compared to knee trauma patients and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Dual specificity phosphatase (DUSP) family has attracted great attention in terms of their regulation of immunology, inflammation, or related bioprocess of autoimmune disease including RA. 18 , 19 , 20 , 21 For instance, DUSP1 deficiency promotes inflammation and bone destruction in collagen‐induced arthritis 18 ; besides, DUSP5 represses autoimmune arthritis by regulating Th17/Treg balance and inactivating osteoclastogenesis in mice. 19 In aspect of DUSP22, although no experimental study been reported, two clinical studies revealed that circulating DUSP22 is closely involved in RA risk and progression.…”
Section: Discussionmentioning
confidence: 99%